Nube híbrida de almacenamiento para análisis de datos (2018)
In this document we propose some mechanisms for the efficient storage of data in a hybrid cloud that serves as a support infrastructure for data analysis systems. For the development of the storage mechanisms, a hybrid cloud was implemented, using the distributed file system of hadoop HDFS. The hybrid cloud implemented consists of a public component and a private component. The public component is called storage on Archive, while the private component makes use of two types of storage, RAMDisk and hard disk, thus providing three options for the provision of data, each with distinctive characteristics. After the hybrid cloud was implemented, tests were performed to compare the performance of each of the components, where the differences in writing times in each of the storage options studied could be evidenced. In accordance with the results of the tests and the evaluation of the costs of each type of storage, an algorithm was developed to determine the most appropriate location of the data within the cloud